Dynamic changes in seagrass assemblages under eutrophication and implications for recovery - Cardoso, P. G. (2004)
Over the last 20 years, loss of seagrass beds, often related with increased eutrophication, became a common problem worldwide. In the Mondego estuary (Portugal), eutrophication has triggered serious biological changes, which led to an overall increase in primary production and to a progressive replacement of seagrass Zostera noltii beds by coarser sediments and opportunistic macroalgae.